Simultaneous removal of NO and SO2 with a micro-bubble gas-liquid dispersion system based on air/H2O2/Na2S2O8 - Xiao, Zhengguo (Environmental technology, 2020)
A novel environment-friendly process was proposed to conduct the simultaneous removal of NO and SO2. In this process, a micro-bubble generator was utilized to generate the micro-bubble gas-liquid dispersion system (MBGLS) by inhaling mixed gas (NO, SO2 and/or air) and absorption liquid. The MBGLS was then sprayed into an oxidation absorption column reactor, in which NO and SO2 were oxidized and absorbed. As the additives, air, H2O2 and/or Na2S2O8 were brought into the MBGLS to investigate their effects on the simultaneous removal of NO and SO2. In addition, the effects of initial pH and temperature of the absorption liquid on the simultaneous removal of NO and SO2 were also explored. The performance of the MBGLS in removing NO and SO2 was excellent. Even if the MBGLS was composed of tap water, NO and SO2, the removal efficiencies of NO and SO2 respectively reached 78% and 94.4%. The additives significantly improved the removal performance of the MBGLS. Under the conditions of pH = 8 and room temperature and the addition of air, SO2 was removed completely and the NO removal efficiency reached 99.5% when Na2S2O8 to H2O2 molar ratio was 0.005/0.05. The effect of the absorbent temperature on the removal of NO and SO2 was insignificant. With the increase in pH, the removal of NO in both H2O2 aqueous solution and Na2S2O8 aqueous solution firstly increased and then decreased, but pH had no effect on the removal of SO2